Preparation method of boric acid etched flower-like bimetallic loaded porous carbon material for lithium-sulfur battery

A bimetallic porous carbon material with Ni-Co diatomic sites addresses slow reaction rates and polysulfide migration in lithium-sulfur batteries, enhancing electron transfer and reaction kinetics to improve energy density and stability.

CN119240658AActive Publication Date: 2025-01-03HARBIN UNIV OF SCI & TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411305133.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-03
Estimated Expiration
2044-09-18

Smart Images

  • Figure CN119240658A_ABST
    Figure CN119240658A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a lithium-sulfur battery positive electrode material, in particular to a preparation method of a boric acid etched flower-like bimetallic loaded porous carbon material for a lithium-sulfur battery. The invention aims to solve the problems of slow oxidation-reduction reaction rate and shuttle effect of a sulfur positive electrode in a lithium-sulfur battery. The method disclosed by the invention comprises the following steps: 1, preparing a nickel-cobalt bimetal organic framework compound (NiCo-ZIF8); (2) preparation of nitrogen-doped porous carbon (NiCo / NPC) with nickel and cobalt double atoms fixed thereon; and 3, preparing the nickel-cobalt diatom-based composite positive electrode material (S / NiCo / NPC). According to the preparation method, cobalt nitrate hexahydrate and nickel nitrate hexahydrate are taken as metal salts, 2-methylimidazole is taken as an organic ligand, boric acid is taken as a pore-forming agent, and the nickel-cobalt-doped flower-shaped porous carbon is prepared through a one-step pyrolysis method, so that the problems of low oxidation reduction rate, positive electrode volume expansion and shuttle effect of a sulfur positive electrode in a lithium-sulfur battery are effectively solved. Meanwhile, the invention provides a new strategy for promoting bidirectional catalysis of a lithium-sulfur system by manipulating the spin delocalization electron effect. The adopted raw materials are rich and low in cost, and the preparation process is simple, convenient and feasible, so that the preparation method has great commercial application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium-sulfur battery positive electrode materials, and in particular to a method for preparing a boric acid-etched flower-shaped bimetallic loaded porous carbon material for lithium-sulfur batteries. Background Art

[0002] Lithium-sulfur batteries have high energy density (2600Wh kg -1 ) and low cost. However, during the discharge process, the electrochemical reaction of the sulfur cathode involves multiple conversion steps. The polysulfides produced after the active material dissolves migrate to the lithium negative electrode under the action of the concentration gradient and form insoluble short-chain lithium sulfide. During charging, these polysulfides will migrate back to the cathode. The shuttle effect generated by this reciprocating behavior seriously depletes the cathode material, and the slow conversion kinetics also cause the actual energy density of lithium-sulfur batteries to be far lower than its theoretical value. Therefore, it is crucial to find a suitable catalyst to accelerate the bidirectional catalytic sulfur redox process and effectively improve the reaction kinetics. In recent years, different catalytic concepts have been introduced into lithium-sulfur cathodes to improve the activity of sulfur cathodes. Among them, atomic-level catalysts are widely used in lithium-sulfur batteries due to their high catalytic activity. However, single-atom catalysts still have problems such as poor selectivity. Therefore, the rational adjustment of active sites at the atomic scale is the key to improving the selective catalytic performance of electrodes. It is feasible to construct catalytic materials with diatomic sites. However, the existing reports have confirmed the catalytic mechanism of lithium-sulfur from the perspective of diatomic selective catalysis, and there are few studies on the electronic state and microstructure between active sites and sulfur. The diatomic center has spin polarization and electron transfer capabilities, which is beneficial to the dynamic transformation of sulfur and provides a continuous site for the complex transformation process of sulfur. Spin polarization catalysis has received extensive attention in the field of electrochemistry as an effective catalytic strategy. Researchers have widely recognized that spin polarization of metal active sites is very effective in accelerating the spin state transition between intermediates in chemical reactions. In particular, spin-polarized metal active sites can promote quantum spin exchange interactions and provide pathways for spin electron transfer in electrocatalytic reactions. Due to the excellent spin polarization and multi-electron transfer capabilities of the dimetallic center, dimetallic active sites have been widely studied. In addition, dimetallic atomic sites can selectively catalyze and improve the electrochemical performance of lithium-sulfur. Therefore, the preparation of a diatomic catalyst that can effectively increase the electrochemical reaction rate of the sulfur cathode is the key to enhancing the cycle stability and energy density of lithium-sulfur batteries. Summary of the invention

[0003] The main purpose of the present invention is to provide a method for preparing a boric acid-etched flower-shaped bimetallic loaded porous carbon material for lithium-sulfur batteries, so as to overcome the problem of slow reaction rates of oxidation reaction and reduction reaction of the sulfur positive electrode of the existing lithium-sulfur battery and effectively inhibit the shuttle effect.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0005] A method for preparing a boric acid-etched flower-shaped bimetallic loaded porous carbon material for lithium-sulfur batteries, specifically comprising the following steps:

[0006] 1. Preparation of NiCo-ZIF8

[0007] 7.50-8.00mmol zinc nitrate hexahydrate and 30.00-33.00mmol 2-methylimidazole were dissolved in 80ml mixed solvent (ethanol / N,N-dimethylformamide, volume ratio 1:1), and magnetically stirred for 30 minutes; 0.45-0.60mmol nickel nitrate hexahydrate and 0.15-0.25mmol cobalt nitrate hexahydrate were added, and stirred for another 30 minutes, and then 7.90-8.20mmol boric acid was added, and stirred for another 15-20 minutes to obtain a suspension; the obtained solution was transferred to a high-pressure reactor, heated to 150-190°C for 12 hours; after cooling to room temperature, centrifuged, washed repeatedly with ethanol and water for 5-10 times, and then dried in an oven at 80°C for 24 hours to obtain white powder NiCo-ZIF8;

[0008] 2. Preparation of NiCo / NPC

[0009] The NiCo-ZIF8 obtained in step 1 was placed in a porcelain boat and heated at 40 mL min -1 The porcelain boat was then heated to 850-950°C (heating rate was 3-5°C min -1 ) annealing for 6 hours; washing the black powder obtained after cooling with water and ethanol several times, and drying it in an oven at 80°C for 24 hours to obtain NiCo / NPC;

[0010] 3. Preparation of Nickel-Cobalt Diatom-Based Composite Cathode Material (S / NiCo / NPC)

[0011] Sulfur and NiCo / NPC obtained in step 2 are mixed in a ratio of 7:3 (wt:wt), and ground in a ball mill for 2-5 hours; then the resulting material is heated in an oven at 155° C. for 12 hours to obtain a S / NiCo / NPC composite material.

[0012] The amount of zinc nitrate hexahydrate in step 1 is 7.50-8.00 mmol, and the amount of 2-methylimidazole is 30.00-33.00 mmol. The ratio of zinc nitrate hexahydrate to 2-methylimidazole is crucial to the morphology of the product. Too little zinc nitrate hexahydrate may result in the failure to form a metal framework; too much zinc nitrate hexahydrate may result in the failure to completely remove the zinc template.

[0013] Furthermore, the amount of nickel nitrate hexahydrate in step 1 is 0.45-0.60 mmol, and the amount of cobalt nitrate hexahydrate is 0.15-0.25 mmol.

[0014] Furthermore, the amount of boric acid in step 1 is 7.90-8.20 mmol. Too little boric acid may result in insufficient etching, and the product may not present a flower-like porous structure; excessive boric acid may result in large and uneven pores, and may not provide suitable metal active sites.

[0015] Furthermore, the stirring time after adding boric acid in step 1 is 15-20 minutes. If the stirring time is insufficient, the boric acid may be unevenly distributed, thereby affecting the uniform porous morphology of the etched product; if the stirring time is too long, the probability of side reactions may increase, affecting the purity of the product.

[0016] Furthermore, the heating temperature of the reaction kettle described in step 1 is 150-190°C.

[0017] Furthermore, the number of repeated washings with ethanol and water in step 1 is 5-10 times. Too few washing times may result in the inability to completely remove the remaining boric acid impurities; too many washing times may result in changes in the surface properties of the material.

[0018] Furthermore, the heating temperature in step 2 is 850-950° C. The boiling point of zinc is 907° C. Too low a temperature may result in incomplete removal of zinc impurities, while too high a temperature may result in collapse of the carbon skeleton.

[0019] Furthermore, the heating rate in step 2 is 3-5°C min -1 A heating rate that is too low may lead to side reactions; a heating rate that is too fast may lead to uneven pore structure.

[0020] Furthermore, the grinding time in step 3 is 2-5 hours. Too short a grinding time may result in the sulfur and the prepared carbon material not being evenly mixed; too long a grinding time may destroy the flower-like porous structure of the prepared carbon material.

[0021] Based on the above technical solution, the following beneficial effects are achieved:

[0022] The present invention proposes a method for preparing a boric acid-etched flower-shaped bimetallic loaded porous carbon material for lithium-sulfur batteries by designing a diatomic spin polarization modulation strategy, and fixes the Ni-Co diatomic catalyst on nitrogen-doped porous carbon to achieve the application of high-performance lithium-sulfur batteries. First, the present invention uses an organic metal framework as a template and uses boric acid for chemical etching to successfully prepare a uniform flower-shaped porous carbon material. The porous structure provides abundant active sites for Ni-Co diatomic doping, and the nitrogen-doped carbon skeleton provides a continuous electron transmission channel, further enhancing the conductivity of the material. This porous structure also helps to reduce the volume expansion of the positive electrode and allows high sulfur loading. Secondly, the present invention utilizes the Ni-Co diatomic spin polarization effect to construct an electron spin channel, which effectively promotes the transmission and exchange of electrons during the electrochemical reaction. The coupling of Ni-Co diatoms changes the distribution of electron spin states and increases the number of spin-polarized electrons. During the reaction, the formation of the spin channel enhances the dp orbital hybridization between Ni-Co diatoms and sulfur, and reduces the activation energy of the Li-S redox reaction. The spin polarization effect not only improves the adsorption capacity of the catalytic material for the intermediate reactants, but also further promotes the dp orbital hybridization, thereby significantly accelerating the reaction kinetics of the battery and improving its cycle performance. In addition, the present invention enhances the electronic interaction between the nickel and cobalt atoms and the reaction intermediates by regulating the d-band centers of the nickel and cobalt atoms. The upward shift of the d-band center enables the nickel-cobalt diatomic catalyst to have more unoccupied 3d orbitals, which can better improve the adsorption with polysulfides and reduce the reaction activation energy. This d-band regulation strategy significantly improves the selectivity and catalytic activity of the catalytic material, effectively promotes the charge transfer and reaction kinetics in the lithium-sulfur battery, and ultimately improves the energy density and cycle stability of the battery. Finally, the present invention realizes the bidirectional catalysis of the redox reactions (SRR and SER) in the lithium-sulfur battery. The Ni-Co diatomic site can accelerate the redox kinetics of sulfur by enhancing the electron transfer and multi-electron transfer capabilities, thereby improving the reaction rate and cycle stability of the battery and inhibiting the polysulfide shuttle effect. This bidirectional catalytic mechanism effectively improves the energy density and charge and discharge efficiency of the battery. In summary, the synergistic effect of Ni-Co diatoms and their nitrogen-doped carbon skeleton makes this material have significant advantages in inhibiting the polysulfide shuttle effect and improving the capacity and cycle stability of lithium-sulfur batteries. Specific performance tests show that the initial discharge capacity of the lithium-sulfur battery at a rate of 0.1 is as high as 1186.4 mAh g -1 After 500 cycles, the capacity decay rate per cycle was only 0.06%, showing excellent long-cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the modified results of the embodiments of the present invention, the accompanying drawings required for describing the comparative examples and embodiments will be briefly introduced below.

[0024] Figure 1 Schematic diagram of the synthesis mechanism of nickel-cobalt diatoms fixed on nitrogen-doped porous carbon materials prepared in Example;

[0025] Figure 2 This is a scanning electron microscope image of nickel-cobalt diatoms fixed on nitrogen-doped porous carbon materials prepared in Example;

[0026] Figure 3 This is a transmission electron microscopy image of nickel-cobalt diatoms fixed on nitrogen-doped porous carbon materials prepared in Example;

[0027] Figure 4 This is a selected area electron diffraction pattern of nickel and cobalt diatoms fixed on nitrogen-doped porous carbon materials prepared in Example;

[0028] Figure 5 This is an X-ray diffraction spectrum of nickel and cobalt diatoms fixed on nitrogen-doped porous carbon materials prepared in Example;

[0029] Figure 6 This is an X-ray diffraction spectrum of a nickel single atom fixed on a nitrogen-doped porous carbon material prepared in Comparative Example 1;

[0030] Figure 7 This is an X-ray diffraction spectrum of a cobalt single atom fixed on a nitrogen-doped porous carbon material prepared in Comparative Example 2;

[0031] Figure 8 This is a Raman spectrum of nickel-cobalt diatoms fixed on nitrogen-doped porous carbon materials prepared in Example;

[0032] Fig. 9 This is a Raman spectrum of a nickel single atom fixed on a nitrogen-doped porous carbon material prepared in Comparative Example 1;

[0033] Fig.10 This is a Raman spectrum of a cobalt single atom fixed on a nitrogen-doped porous carbon material prepared in Comparative Example 2;

[0034] Fig.11 Full scan X-ray photoelectron spectroscopy of nickel and cobalt diatoms fixed on nitrogen-doped porous carbon materials prepared in Example;

[0035] Fig.12 This is a C1s graph of the X-ray photoelectron spectrum of the nickel-cobalt diatoms fixed on the nitrogen-doped porous carbon material prepared in Example;

[0036] Fig.13 N1s graph of X-ray photoelectron spectrum of nickel-cobalt diatoms fixed on nitrogen-doped porous carbon material prepared in Example;

[0037] Fig.14The Tafel curves of different positive electrodes of lithium-sulfur batteries prepared and assembled in Example, Comparative Example 1 and Comparative Example 2, A is the Tafel curve of Example, B is the Tafel curve of Comparative Example 1, and C is the Tafel curve of Comparative Example 2;

[0038] Fig.15 Cyclic voltammetry curves of lithium-sulfur batteries prepared and assembled for Example, Comparative Example 1 and Comparative Example 2, A is the cyclic voltammetry curve of Example, B is the cyclic voltammetry curve of Comparative Example 1, and C is the cyclic voltammetry curve of Comparative Example 2;

[0039] Fig.16 The rate performance diagram of the lithium-sulfur battery prepared and assembled in the embodiment;

[0040] Fig.17 The cycle performance diagrams of the lithium-sulfur batteries assembled in Example, Comparative Example 1 and Comparative Example 2 at a rate of 0.5 are shown, where A is the cycle performance of the example, B is the cycle performance of Comparative Example 1, and C is the cycle performance of Comparative Example 2;

[0041] Fig.18 The charge and discharge curves of the lithium-sulfur batteries prepared and assembled in Example, Comparative Example 1 and Comparative Example 2 are shown in Figure 1, where A is the charge and discharge curve of Example 1, B is the charge and discharge curve of Comparative Example 1, and C is the charge and discharge curve of Comparative Example 2;

[0042] Fig.19 Performance diagram of the lithium-sulfur battery assembled in the embodiment after 500 cycles at 1 rate;

[0043] Fig. 20 Impedance diagrams of lithium-sulfur batteries assembled in Example, Comparative Example 1 and Comparative Example 2 after 500 cycles, A is the impedance diagram of Example after 500 cycles, B is the impedance diagram of Comparative Example 1 after 500 cycles, and C is the impedance diagram of Comparative Example 2 after 500 cycles;

[0044] Fig.21 The projected density of states (PDOS) calculation diagram of nickel-cobalt diatoms fixed on nitrogen-doped porous carbon materials prepared in Example;

[0045] Fig. 22 Figures are the differential charge density calculation diagrams of NiCo / NPC, Ni / NPC and Co / NPC prepared in Example, Comparative Example 1 and Comparative Example 2, respectively. A is the differential charge density calculation diagram of Example, B is the differential charge density calculation diagram of Comparative Example 1, and C is the differential charge density calculation diagram of Comparative Example 2;

[0046] Fig.23 Magnetic hysteresis loops of NiCo / NPC, Ni / NPC and Co / NPC prepared in Example, Comparative Example 1 and Comparative Example 2, respectively, A is the hysteresis loop of Example, B is the hysteresis loop of Comparative Example 1, and C is the hysteresis loop of Comparative Example 2;

[0047] Fig.24 The Gibbs free energy curves of NiCo / NPC, Ni / NPC and Co / NPC prepared in Example, Comparative Example 1 and Comparative Example 2, respectively, A is the Gibbs free energy curve of Example, B is the Gibbs free energy curve of Comparative Example 1, and C is the Gibbs free energy curve of Comparative Example 2. DETAILED DESCRIPTION

[0048] The above contents of the present invention are further described in detail below through embodiments, but the subject matter of the present invention is not limited to the following embodiments, and all technologies realized based on the above contents of the present invention belong to the scope of the present invention.

[0049] Experimental drugs

[0050]

[0051] Experimental equipment

[0052]

[0053] The above contents of the present invention are further described in detail below through embodiments, but the subject matter of the present invention is not limited to the following embodiments, and all technologies realized based on the above contents of the present invention belong to the scope of the present invention.

[0054] Example:

[0055] 1. Preparation of NiCo-ZIF8

[0056] 7.50-8.00mmol zinc nitrate hexahydrate and 30.00-33.00mmol 2-methylimidazole were dissolved in 80ml mixed solvent (ethanol / N,N-dimethylformamide, volume ratio 1:1), and magnetically stirred for 30 minutes; 0.45-0.60mmol nickel nitrate hexahydrate and 0.15-0.25mmol cobalt nitrate hexahydrate were added, and stirred for another 30 minutes, and then 7.90-8.20mmol boric acid was added, and stirred for another 15-20 minutes to obtain a suspension; the obtained solution was transferred to a high-pressure reactor, heated to 150-190°C for 12 hours; after cooling to room temperature, centrifuged, washed repeatedly with ethanol and water for 5-10 times, and then dried in an oven at 80°C for 24 hours to obtain white powder NiCo-ZIF8;

[0057] 2. Preparation of NiCo / NPC

[0058] The NiCo-ZIF8 obtained in step 1 was placed in a porcelain boat and heated at 40 mL min -1The porcelain boat was then heated to 850-950°C (heating rate was 3-5°C min -1 ) annealing for 6 hours; washing the black powder obtained after cooling with water and ethanol several times, and drying it in an oven at 80°C for 24 hours to obtain NiCo / NPC;

[0059] 3. Preparation of Nickel-Cobalt Diatom-Based Composite Cathode Material (S / NiCo / NPC)

[0060] Sulfur and NiCo / NPC obtained in step 2 are mixed in a ratio of 7:3 (wt:wt), and ground in a ball mill for 2-5 hours; then the resulting material is heated in an oven at 155° C. for 12 hours to obtain a S / NiCo / NPC composite material.

[0061] Comparative Example 1:

[0062] 1. Preparation of Nickel Metal Organic Framework Compound (Ni-ZIF8)

[0063] 7.50-8.00mmol zinc nitrate hexahydrate and 30.00-33.00mmol 2-methylimidazole were dissolved in 80ml mixed solvent (ethanol / N,N-dimethylformamide, volume ratio 1:1), and magnetically stirred for 30 minutes; 0.45-0.60mmol nickel nitrate hexahydrate was added, and stirred for another 30 minutes, and then 7.90-8.20mmol boric acid was added, and stirred for another 15-20 minutes to obtain a suspension; the obtained solution was transferred to a high-pressure reactor, heated to 150-190°C for 12 hours; after cooling to room temperature, centrifuged, washed repeatedly with ethanol and water for 5-10 times, and then dried in an oven at 80°C for 24 hours to obtain white powder Ni-ZIF8;

[0064] 2. Preparation of Ni single atoms fixed on nitrogen-doped porous carbon (Ni / NPC)

[0065] The Ni-ZIF8 obtained in step 1 was placed in a porcelain boat and heated at 40 mL min -1 The porcelain boat was then heated to 850-950°C (heating rate was 3-5°C min -1 ) annealing for 6 hours; washing the black powder obtained after cooling with water and ethanol several times, and drying it in an oven at 80°C for 24 hours to obtain Ni / NPC;

[0066] 3. Preparation of Nickel Single Atom-Based Composite Cathode Material (S / Ni / NPC)

[0067] Sulfur and Ni / NPC obtained in step 2 were mixed in a ratio of 7:3 (wt:wt), and ground in a ball mill for 2-5 hours; the resulting material was then heated in an oven at 155° C. for 12 hours to obtain a S / Ni / NPC composite material.

[0068] Comparative Example 2:

[0069] 1. Preparation of Cobalt Metal Organic Framework Compound (Co-ZIF8)

[0070] 7.50-8.00mmol zinc nitrate hexahydrate and 30.00-33.00mmol 2-methylimidazole were dissolved in 80ml mixed solvent (ethanol / N,N-dimethylformamide, volume ratio 1:1), and magnetically stirred for 30 minutes; 0.45-0.60mmol cobalt nitrate hexahydrate was added, and stirred for another 30 minutes, and then 7.90-8.20mmol boric acid was added, and stirred for another 15-20 minutes to obtain a suspension; the obtained solution was transferred to a high-pressure reactor, heated to 150-190°C for 12 hours; after cooling to room temperature, centrifuged, washed repeatedly with ethanol and water for 5-10 times, and then dried in an oven at 80°C for 24 hours to obtain white powder Co-ZIF8;

[0071] 2. Preparation of Cobalt Single Atoms Fixed on Nitrogen-doped Porous Carbon (Co / NPC)

[0072] The Co-ZIF8 obtained in step 1 was placed in a porcelain boat and heated at 40 mL min -1 The porcelain boat was then heated to 850-950°C (heating rate was 3-5°C min -1 ) annealing for 6 hours; washing the black powder obtained after cooling with water and ethanol several times, and drying it in an oven at 80°C for 24 hours to obtain Co / NPC;

[0073] 3. Preparation of Cobalt Single Atom-Based Composite Cathode Material (S / Co / NPC)

[0074] Sulfur and Co / NPC obtained in step 2 were mixed in a ratio of 7:3 (wt:wt), and ground in a ball mill for 2-5 hours; the resulting material was then heated in an oven at 155° C. for 12 hours to obtain a S / Co / NPC composite material.

[0075] The difference between Comparative Example 1, Comparative Example 2 and the embodiment is mainly that the metal atoms fixed on the nitrogen-doped porous carbon are different. The composite materials synthesized by Comparative Example 1, Comparative Example 2 and the embodiment and the lithium-sulfur battery assembled therefrom are characterized as follows:

[0076] Figure 1Schematic diagram of the synthesis mechanism of nickel-cobalt diatoms fixed on nitrogen-doped porous carbon materials prepared in Example 1. Nickel-cobalt doped hierarchical porous carbon was prepared by a one-step pyrolysis method using cobalt nitrate hexahydrate and nickel nitrate hexahydrate as metal salts, 2-methylimidazole as an organic ligand, and boric acid as a pore-forming agent.

[0077] Figure 2 The scanning electron microscope image of the prepared nickel-cobalt diatoms fixed on the nitrogen-doped porous carbon material shows that the NiCo / NPC has a hierarchical porous morphology and presents a unique spherical flower-like structure, which provides abundant sites for the doping of nickel and cobalt atoms.

[0078] Figure 3 This is a transmission electron microscopy image of the nickel-cobalt diatoms fixed on the nitrogen-doped porous carbon material prepared in the example. The transmission electron microscopy image further observed that NiCo / NPC has a clear spherical porous structure.

[0079] Figure 4 This is a selected area electron diffraction pattern of nickel-cobalt diatoms fixed on nitrogen-doped porous carbon materials prepared in Example 1. The selected area electron diffraction pattern further confirms that NiCo / NPC is a porous carbon sphere, and no lattice fringes are found, confirming that the metal atoms have no obvious agglomeration.

[0080] Figure 5 The X-ray diffraction spectrum of the prepared nickel-cobalt diatomic immobilization on the nitrogen-doped porous carbon material is shown in Figure 1. The X-ray diffraction pattern of NiCo / NPC shows a broad diffraction peak of graphitization at 26° on the (0 0 2) plane.

[0081] Figure 6 This is the X-ray diffraction spectrum of the nickel single atom fixed on the nitrogen-doped porous carbon material prepared in Comparative Example 1. The X-ray diffraction pattern of Ni / NPC shows a broad diffraction peak of graphitization at 26° on the (0 0 2) plane.

[0082] Figure 7 This is the X-ray diffraction spectrum of the cobalt single atom fixed on the nitrogen-doped porous carbon material prepared in Comparative Example 2. The X-ray diffraction pattern of Co / NPC shows a broad diffraction peak of graphitization at 26° on the (0 0 2) plane.

[0083] Figure 8 The Raman spectrum of the nickel-cobalt diatomic immobilized on the nitrogen-doped porous carbon material prepared in Example 1. The Raman spectrum of NiCo / NPC is at 1335 cm -1 and 1580cm -1 There are two different peaks, corresponding to the D peak and G peak of carbon materials.

[0084] Fig. 9This is the Raman spectrum of the nickel single atom fixed on the nitrogen-doped porous carbon material prepared in Comparative Example 1. The Raman spectrum of Ni / NPC is at 1335 cm -1 and 1580cm -1 There are two different peaks, corresponding to the D peak and G peak of carbon materials.

[0085] Fig.10 This is the Raman spectrum of the cobalt single atom fixed on the nitrogen-doped porous carbon material prepared in Comparative Example 2. The Raman spectrum of Co / NPC is at 1335 cm -1 and 1580cm -1 There are two different peaks, corresponding to the D peak and G peak of carbon materials.

[0086] Fig.11 Full scan X-ray photoelectron spectrum of nickel-cobalt diatoms fixed on nitrogen-doped porous carbon materials prepared in Example. Through analysis, the presence of nickel, cobalt, nitrogen and carbon elements can be seen in the full scan X-ray photoelectron spectrum of NiCo / NPC, confirming that the prepared NiCo / NPC meets expectations.

[0087] Fig.12 The C1s graph of the X-ray photoelectron spectrum of the NiCo diatomic immobilization on the nitrogen-doped porous carbon material prepared in the example. According to the C1s spectrum of NiCo / NPC, there are obvious characteristic peaks at 284.8 and 286.2 eV, corresponding to the CC bond and the CN bond, respectively.

[0088] Fig.13 The N1s diagram of the X-ray photoelectron spectrum of the prepared nickel-cobalt diatoms fixed on the nitrogen-doped porous carbon material. According to the N1s spectrum of NiCo / NPC, the N1s spectrum of the sample can be decomposed into four types, with different peaks at 400.6, 401.2, 398.6 and 399.8 eV, corresponding to pyridine-N, graphite-N, metal-N and pyridine-N, respectively. These findings confirm that nickel and cobalt coordinate with nitrogen as one atom to form Ni-Co-N6.

[0089] Fig.14 The Tafel curves of different positive electrodes of lithium-sulfur batteries assembled in Example, Comparative Example 1 and Comparative Example 2 are shown, A is the Tafel curve of Example, B is the Tafel curve of Comparative Example 1, and C is the Tafel curve of Comparative Example 2. The Tafel curve of the lithium-sulfur battery assembled from S / NiCo / NPC shows that, compared with S / Ni / NPC and S / Co / NPC, the lithium-sulfur battery assembled from NiCo / NPC has the largest exchange current density and the lowest Tafel slope, which accelerates the redox conversion of sulfur.

[0090] Fig.15Cyclic voltammetry curves of lithium-sulfur batteries prepared and assembled for Example, Comparative Example 1 and Comparative Example 2. A is the cyclic voltammetry curve of Example, B is the cyclic voltammetry curve of Comparative Example 1, and C is the cyclic voltammetry curve of Comparative Example 2. The figure shows the cyclic voltammetry curve at a scan rate of 0.1 mV s -1 The cyclic voltammetry curves of different lithium-sulfur batteries assembled from three materials, S / NiCo / NPC, S / Ni / NPC and S / Co / NPC, are shown. Due to the sufficient and rapid electrochemical redox reaction of sulfur, the S / NiCo / NPC cathode has the highest current density and the smallest polarization voltage gap.

[0091] Fig.16 The figure is the rate performance diagram of the lithium-sulfur battery assembled in the example. The maximum discharge capacities of the lithium-sulfur battery assembled from S / NiCo / NPC at 0.1, 0.2, 0.5, 1 and 2 rates are 1253.6, 1046.2, 945.0, 885.3 and 727.0 mAh g -1 When the rate is restored to 0.5 times, 944.3 mAh g -1 High capacity and good reversibility.

[0092] Fig.17 The cycle performance diagrams of the lithium-sulfur batteries assembled in Example, Comparative Example 1 and Comparative Example 2 at 0.5 times rate are shown, A is the cycle performance of Example, B is the cycle performance of Comparative Example 1, and C is the cycle performance of Comparative Example 2. Compared with S / Ni / NPC and S / Co / NPC, S / NiCo / NPC has better cycle stability, significantly smaller capacity attenuation rate, and higher initial capacity.

[0093] Fig.18 The charge and discharge curves of the lithium-sulfur batteries prepared and assembled in Example, Comparative Example 1 and Comparative Example 2 are shown in Figure 1. A is the charge and discharge curve of Example 1, B is the charge and discharge curve of Comparative Example 1, and C is the charge and discharge curve of Comparative Example 2. Compared with S / Ni / NPC and S / Co / NPC, the initial discharge capacity of S / NiCo / NPC can reach up to 1099 mAh g at a rate of 0.5. -1 , the overpotential is also smaller.

[0094] Fig.19 The performance diagram of the lithium-sulfur battery assembled in the embodiment after 500 cycles at 1 rate. The lithium-sulfur battery assembled with S / NiCo / NPC provides 1186.4 mAh g -1 The high initial capacity and capacity retention rate after 500 cycles are 78%.

[0095] Fig. 20Impedance diagrams of lithium-sulfur batteries assembled in Example, Comparative Example 1 and Comparative Example 2 after 500 cycles, A is the impedance diagram of Example after 500 cycles, B is the impedance diagram of Comparative Example 1 after 500 cycles, and C is the impedance diagram of Comparative Example 2 after 500 cycles. The EIS impedances after cycles corresponding to different cathodes show that after 500 cycles, the charge transfer impedance of the S / NiCo / NPC cathode is lower, because the redox reaction of the sulfur cathode is well maintained as the number of cycles increases.

[0096] Fig.21 The projected density of states (PDOS) calculation diagram of the nickel-cobalt diatoms fixed on the nitrogen-doped porous carbon material prepared in the example. The 3d orbitals of nickel and cobalt in NiCo / NPC strongly resonate near the Fermi level, indicating the dd orbital coupling between Ni-Co.

[0097] Fig. 22 The differential charge density calculation diagrams of NiCo / NPC, Ni / NPC and Co / NPC prepared in Example, Comparative Example 1 and Comparative Example 2, respectively, A is the differential charge density calculation diagram of Example, B is the differential charge density calculation diagram of Comparative Example 1, and C is the differential charge density calculation diagram of Comparative Example 2. Compared with Ni / NPC and Co / NPC, the 3d electrons of nickel and cobalt in NiCo / NPC are delocalized and attracted by the surrounding nitrogen atoms to form an electron-rich density region, which is the result of partial transfer of nickel and cobalt electrons to the coordinated nitrogen atoms.

[0098] Fig.23 The hysteresis loops of NiCo / NPC, Ni / NPC and Co / NPC prepared in Example, Comparative Example 1 and Comparative Example 2, respectively, A is the hysteresis loop of Example, B is the hysteresis loop of Comparative Example 1, and C is the hysteresis loop of Comparative Example 2. The saturation magnetization of NiCo / NPC is 4emu g -1 , which is 20 times higher than that of Ni / NPC and Co / NPC, because NiCo / NPC has more spin electrons.

[0099] Fig.24 The Gibbs free energy curves of NiCo / NPC, Ni / NPC and Co / NPC prepared in Example, Comparative Example 1 and Comparative Example 2, respectively, A is the Gibbs free energy curve of Example, B is the Gibbs free energy curve of Comparative Example 1, and C is the Gibbs free energy curve of Comparative Example 2. The ΔG value of the process of converting Li2S2 to Li2S on NiCo / NPC is 0.820eV, while that of Ni / NPC is 0.894eV and that of Co / NPC is 0.990eV. NiCo / NPC has the lowest Gibbs free energy, which verifies the synergistic catalytic and selective catalytic activity of NiCo / NPC.

[0100] In summary, integrating Ni-Co atomic active sites into layered porous carbon helps to increase the redox reaction rate of the sulfur cathode and inhibit the shuttling effect. The enhanced electrochemical activity of NiCo / NPC is due to the upward movement of the d-band caused by the transfer of electrons from nickel to nitrogen, which reduces the antibonding orbital filling and promotes the adsorption of polysulfides. In addition, the coupling of nickel and cobalt sites in the cathode induces the difference in spin states, creating a spin channel for electron transfer in the sulfur redox reaction, thereby improving the stability of lithium-sulfur battery cycles. This manipulation of spin-delocalized electronic effects represents a new strategy to promote bidirectional catalysis in lithium-sulfur systems. Therefore, based on the above advantages, the nickel-cobalt diatomic-based composite cathode material for lithium-sulfur batteries applied in the present invention shows significant application potential and broad development value in various actual energy storage systems.

Claims

1. A method for preparing a boric acid-etched flower-shaped bimetallic porous carbon material for lithium-sulfur batteries, characterized in that A method for preparing a boric acid-etched flower-shaped bimetallic loaded porous carbon material for lithium-sulfur batteries is carried out according to the following steps:

1. Preparation of NiCo-ZIF8 7.50-8.00mmol zinc nitrate hexahydrate and 30.00-33.00mmol 2-methylimidazole were dissolved in 80ml mixed solvent (ethanol / N,N-dimethylformamide, volume ratio 1:1), and magnetically stirred for 30 minutes; 0.45-0.60mmol nickel nitrate hexahydrate and 0.15-0.25mmol cobalt nitrate hexahydrate were added, and stirred for another 30 minutes, and then 7.90-8.20mmol boric acid was added, and stirred for another 15-20 minutes to obtain a suspension; the obtained solution was transferred to a high-pressure reactor, heated to 150-190°C for 12 hours; after cooling to room temperature, centrifuged, washed repeatedly with ethanol and water for 5-10 times, and then dried in an oven at 80°C for 24 hours to obtain white powder NiCo-ZIF8; 2. Preparation of NiCo / NPC The NiCo-ZIF8 obtained in step 1 was placed in a porcelain boat and heated at 40 mL min -1 The porcelain boat was then heated to 850-950°C (heating rate was 3-5°C min -1 ) annealing for 6 hours; washing the black powder obtained after cooling with water and ethanol several times, and drying it in an oven at 80°C for 24 hours to obtain NiCo / NPC; 3. Preparation of Nickel-Cobalt Diatom-Based Composite Cathode Material (S / NiCo / NPC) Sulfur and NiCo / NPC obtained in step 2 were mixed in a ratio of 7:3 (wt:wt), and ground in a ball mill for 2-5 hours; the resulting material was then heated in an oven at 155° C. for 12 hours to obtain a S / NiCo / NPC composite material.

2. The method for preparing a boric acid-etched flower-shaped bimetallic porous carbon material for lithium-sulfur batteries according to claim 1, characterized in that The amount of zinc nitrate hexahydrate in step 1 is 7.50-8.00 mmol, and the amount of 2-methylimidazole is 30.00-33.00 mmol.

3. The method for preparing a boric acid-etched flower-shaped bimetallic porous carbon material for lithium-sulfur batteries according to claim 1, characterized in that The amount of nickel nitrate hexahydrate in step 1 is 0.45-0.60 mmol, and the amount of cobalt nitrate hexahydrate is 0.15-0.25 mmol.

4. The method for preparing a boric acid-etched flower-shaped bimetallic-loaded porous carbon material for lithium-sulfur batteries according to claim 1, characterized in that The amount of the boric acid in step 1 is 7.90-8.20 mmol.

5. The method for preparing a boric acid-etched flower-shaped bimetallic porous carbon material for lithium-sulfur batteries according to claim 1, characterized in that The stirring time after adding boric acid in step 1 is 15-20 minutes.

6. The method for preparing a boric acid-etched flower-shaped bimetallic porous carbon material for lithium-sulfur batteries according to claim 1, characterized in that The heating temperature of the reactor described in step 1 is 150-190°C.

7. The method for preparing a boric acid-etched flower-shaped bimetallic-loaded porous carbon material for lithium-sulfur batteries according to claim 1, characterized in that The number of repeated washings with ethanol and water in step 1 is 5-10 times.

8. The method for preparing a boric acid-etched flower-shaped bimetallic porous carbon material for lithium-sulfur batteries according to claim 1, characterized in that The heating temperature in step 2 is 850-950°C.

9. The method for preparing a boric acid-etched flower-shaped bimetallic porous carbon material for lithium-sulfur batteries according to claim 1, characterized in that The heating rate in step 2 is 3-5℃min -1 .

10. The method for preparing a boric acid-etched flower-shaped bimetallic-loaded porous carbon material for lithium-sulfur batteries according to claim 1, characterized in that The grinding time described in step 3 is 2-5 hours.

Citation Information

Patent Citations

  • Preparation method of NiCo2S4-coated porous carbon skeleton for positive electrode material of lithium-sulphur battery

    CN109378449A

  • Lithium-sulfur battery positive host material as well as preparation method and application thereof

    CN111463413A

  • Ni-N and Co-N loaded double active site doped hollow carbon sphere catalyst as well as preparation method and application thereof

    CN115020918A

  • Three-dimensional porous MOF (Metal Organic Framework) derived nickel cobalt phosphide-nitrogen doped carbon composite material as well as preparation method and application thereof

    CN118098840A

  • Nondestructive inspection system using neutron ray and x-ray

    KR102157233B1